Yoga-induced Valsalva Retinopathy - Drishti Kaushal; Sakshi Kapila; Arti Sareen Gupta; Arushi Rattan (Delhi Journal of Ophthalmology)
Valsalva retinopathy (VR) is a preretinal hemorrhage due to increase in intraabdominal or intrathoracic pressure resulting in rupture of superficial retinal capillaries. History of a preceding event/condition that results in an increase in intra-thoracic or intra-abdominal pressure is usually given by the patient such as practicing yoga, weight-lifting exercises, excessive coughing, and constipation. A 42-year-old female patient presented with a chief complaint of decreased vision in the left eye for 1 week. She gave a history of practicing Baba Ramdev recommended “Anuloma Pranayam,” a practice of Hatha Yoga. The best-corrected visual acuity of the patient was 1/60 in the affected eye. On fundus examination, a preretinal hemorrhage was observed in the macular area. Based on the history, examination, and investigations, a diagnosis of VR was made. Such hemorrhages can be a result of various Valsalva maneuvers but other causes of retinal hemorrhages need to be ruled out before coming to this diagnosis. The disease has a spontaneous resolution within weeks to months.